Development of an antibacterial polypropylene/polyurethane composite membrane for invisible orthodontics application - Yang, Feng; Wu, Chenyi; Jiang, Yuanzhang; Tan, Lin; Shu, Rui (Frontiers in Bioengineering and Biotechnology, 2023)
In virtue of the advantages, such as aesthetics, designability, convenient removal, and comfortable experience, invisible orthodontics (IO) have been widely recognized and accepted by the public. However, most of the membranes currently used for IO only meet the requirement of shape retention. Other vital functions, like antibacterial and antifouling activities, are neglected. Herein, antibacterial composite membranes (ACMs) containing polypropylene (PP), thermoplastic polyurethane (TPU) and poly (hexamethylene guanidine) hydrochloride-sodium stearate (PHMG-SS) were facilely manufactured through the hot-pressing membrane forming technology. ACMs were conferred with favorable transparency (~70% in the visible light range) and excellent antibacterial ability. Experiment results demonstrated that bactericidal rates of ACMs against Staphylococcus aureus, Escherichia coli and Streptococcus mutans were larger than 99.99%. Noticeably, the amount of protein adhered on the surface of ACMs was only 28.1 μg/cm 2 , showing ideal antifouling performance. Collectively, the mutifunctional ACMs in the study are expected to be prominent alternatives for existing IO.